2007
DOI: 10.4049/jimmunol.179.6.4272
|View full text |Cite
|
Sign up to set email alerts
|

Down-Modulation of CXCR3 Surface Expression and Function in CD8+ T Cells from Cutaneous T Cell Lymphoma Patients

Abstract: Viruses can escape destruction by the immune system by exploitation of the chemokine-chemokine receptor system. It is less established whether human cancers can adopt similar strategies to evade immunologic control. In this study, we show that advanced cutaneous T cell lymphoma (CTCL) is associated with selective and efficient inactivation of CXCR3-dependent T cell migration. Our studies demonstrate that this alteration is at least in part due to CXCR3 down-regulation in vivo by elevated serum levels of CXCR3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although these chemokines are known to attract T cells to sites of inflammation, they are also known to be highly expressed during melanoma and other cancer burdens, allowing malignant cancer cells to migrate to distant nodes (45, 62). CXCR3 + T cells in the presence of these high chemokines also can lose CXCR3 expression preventing the cells from migrating into the cancerous tissue (63). In fact, we see high levels of these chemokines during recurrence and loss of CXCR3 on the tumor-specific CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although these chemokines are known to attract T cells to sites of inflammation, they are also known to be highly expressed during melanoma and other cancer burdens, allowing malignant cancer cells to migrate to distant nodes (45, 62). CXCR3 + T cells in the presence of these high chemokines also can lose CXCR3 expression preventing the cells from migrating into the cancerous tissue (63). In fact, we see high levels of these chemokines during recurrence and loss of CXCR3 on the tumor-specific CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CXCR3 is downregulated in several pathological conditions, in which serum sHLA-G levels are increased, such as allergy[45], T cell lymphoma[46]and multiple sclerosis [47]. Conversely, CXCR3 has been found to be upregulated in diseased associated with decerased levels of serum sHLA-G, such as rheumatoid arthritis and lupus [48].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of T-cell-expressed CXCR3 is illustrated by the observation that patients with cutaneous T-cell lymphomas had decreased surface expression of CXCR3 on circulating CD8 + T cells [39]. Although CXCR3 transcript levels were normal, surface receptor expression was diminished, and, not surprisingly, these cells migrated poorly to CXCR3 ligands.…”
Section: Cxcr3 Ligandsmentioning
confidence: 98%